Evaluation of swab materials in forensic DNA testing: a systematic review - Jillian Conte; Lauren A. Morgan; Tracey L. Johnson (Egyptian Journal of Forensic Sciences)
Abstract Background Forensic biology technology advances quickly: DNA typing technologies are increasing in sensitivity, resolving DNA mixtures is improving, and isolating and targeting male-specific DNA continues to become more streamlined. However, one part of the forensic biology workflow that has remained relatively unchanged is the type of swab used to collect samples. Swab composition technology has advanced, yet cotton swabs continue to be the primary choice for biological evidence collection. This report describes the results of a systematic literature review and analysis to determine which swab types work best for collecting biological evidence. Results An article was included in the review if it is an original research article, discusses more than one swab brand or material, has a forensic focus, and reports data from real-time PCR (qPCR) or forensic DNA typing. Articles were excluded if they were not primary research (literature/systematic review) or not written in the English language or if the product was a thesis or dissertation. The literature was collected through Web of Science, PubMed, and EBSCO searches in September 2023. Removal of duplicates and selection of articles were performed in Rayyan. Additional articles were identified in the bibliographies of initially selected articles. The analysis was organized by substrate (porous, n = 9; nonporous, n = 8) and source of DNA (n = 5). Forty-one substrate-DNA source combinations have been researched, and 13 substrate-DNA source combinations have an identified best-performing swab type. There are several limitations in the study, including heterogeneity of data and selection bias during the literature search and study identification. Conclusions Primary conclusions are (1) DNA extraction chemistry needs to be considered with swab type, (2) swabs made of the same material do not perform the same when compared to each other, and (3) inter-operator swabbing is not different. This work highlights research gaps that should be addressed for substrate-DNA source combinations and can guide practitioners in making evidence-based decisions on implementing different swab types into their workflow.